Effects of postmortem time and storage fluid on the material properties of bovine liver parenchyma in tension. (November 2018) - Dunford, Kristin M.; LeRoith, Tanya; Kemper, Andrew R.
Abstract: In motor vehicle collisions (MVCs), liver injuries are one of the most frequently reported types of abdominal organ trauma. Although finite element models are utilized to evaluate the risk of sustaining an abdominal organ injury in MVCs, these models must be validated based on biomechanical data in order to accurately assess injury risk. Given that previous studies that have quantified the tensile failure properties of human liver parenchyma have been limited to testing at 48 h postmortem, it is currently unknown how the material properties change between time of death and 48 h postmortem. Therefore, the objective of this study was to quantify the effects of postmortem degradation on the tensile material properties of bovine liver parenchyma with increasing postmortem time when stored in DMEM or saline. A total of 148 uniaxial tension tests were successfully conducted on parenchyma samples of fourteen bovine livers acquired immediately after death. Liver tissue was submerged in DMEM or saline and kept cool during sample preparation and storage. Twelve livers were stored as large blocks of tissue, while two livers were stored as small blocks and slices. Tension tests were performed on multiple dog-bone samples from each liver at three time points: ~6 h, ~24 h, and ~48 h postmortem. The data were then analyzed using a Linear Mixed Effect Model to determine if there were significant changes in the failure stress, failure strain, and modulus with respect to postmortem time. The results of the current study showed that the failure strain of bovine liver parenchyma decreased significantly between 6 h and 48 h after death when stored as large blocks in saline and refrigerated. Conversely, neither the failure stress nor failure strain changed significantly with respect to postmortem time when stored as large blocks in DMEM. The modulus did not change significantly with respect to postmortem time for tissue stored as large blocks in either saline or DMEM. Cellular disruption increased with postmortem time for tissue stored as large blocks, with tissue stored in saline showing the greatest increase at each time point. In addition, preliminary results indicated that reducing the tissue storage size had a negative effect on the material properties and cellular architecture. Overall, this study illustrated that the effects of postmortem liver degradation varied with respect to the preservation fluid, storage time, and storage block size.